2010
DOI: 10.1177/003335491012500317
|View full text |Cite
|
Sign up to set email alerts
|

Health Impact Assessment of Environmental Tobacco Smoke in European Children: Sudden Infant Death Syndrome and Asthma Episodes

Abstract: This article by Boldo et al. demonstrates that in Europe, exposure to environmental tobacco smoke (ETS) caused an estimated 24% to 32% of sudden infant death syndrome (SIDS) cases and increased the number of asthma episodes by 7% to 11% in children younger than 14 years of age. The major source of exposure to ETS among children is smoking by parents and other household members. The European countries in this study included wealthy countries such as Austria, Denmark, Germany, and the United Kingdom as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…We also could not estimate the disease burden in infants because we could not obtain data on the prevalence of exposure to maternal smoking in utero. Exposure to maternal smoking in utero is suspected to be associated with low birth weight, sudden infant death syndrome, asthma, and lower respiratory tract infections in children (Anderson & Cook 1997;Cook & Strachan 1997;Boldo et al 2010). In a previous study, the proportion of deaths in infants among all AD ets in white non-smokers was approximately 1.6 %, with a maternal smoking exposure prevalence rate in utero of 2.8 % in the United States in 2006 (Max et al 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We also could not estimate the disease burden in infants because we could not obtain data on the prevalence of exposure to maternal smoking in utero. Exposure to maternal smoking in utero is suspected to be associated with low birth weight, sudden infant death syndrome, asthma, and lower respiratory tract infections in children (Anderson & Cook 1997;Cook & Strachan 1997;Boldo et al 2010). In a previous study, the proportion of deaths in infants among all AD ets in white non-smokers was approximately 1.6 %, with a maternal smoking exposure prevalence rate in utero of 2.8 % in the United States in 2006 (Max et al 2012).…”
Section: Discussionmentioning
confidence: 96%
“…According to summary reports of several expert agency panels, including the US Surgeon General and the California Environmental Protection Agency, ETS has been proven to be associated with a higher risk of coronary heart disease, stroke, lung cancer, and respiratory diseases in adults (California Environmental Protection Agency: Air Resources Board 2005; General 2006). The US Surgeon General also suggested that exposure to ETS might be causally associated with various health effects in children, including low birth weight, sudden infant death syndrome, asthma, and lower respiratory tract infections (General 2006;Boldo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The sizeable lower 95% CI estimate underscores the significance of SHS exposure as an environmental risk factor for infant health. The assumed pooled OR used associating SHS in the home with SIDS (OR=3.15) is based on postnatal maternal smoking and has been validated as a proxy for all infant exposure to SHS 34. The RCP-UK meta-analysis, and resulting pooled OR, was inclusive of studies reviewed by the US Surgeon General in 2006 as well as 75 additional studies including studies from the USA; as such, it was appropriate to apply this OR to US SIDS data.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] In utero tobacco exposure increases risk of adverse fetal outcomes and can have long-lasting adverse health effects for the child. [16][17][18][19][20][21][22][23][24][25][26][27][28] Although sorting out in utero from postnatal effects is challenging, emerging data points to secondhand tobacco smoke exposure as an independent risk factor for neurobehavioral disorders (including attention-deficit/hyperactivity disorder, learning disabilities, and conduct disorders), [29][30][31] decreased glomerular filtration rate in adolescents, 32 and preclinical atherosclerosis in adolescents.…”
Section: Introductionmentioning
confidence: 99%